نمذجة معامل الشكل لأشجار الصنوبر البروتي Pinus brutia Ten. في غابات ربيعة في شمال اللاذقية - علي, وائل; الشاطر, زهير (Latakia University Journal -Biological Sciences Series, 2014)
يعتبر تقدير حجوم الأشجار والمجموعات الحرجية حجر الأساس في إدارة وتنظيم الغابات الإنتاجية (de Miguel et al., 2012). إنّ التقدير الصحيح لحجوم الأشجار يحتاج إلى أخذ الاختلافات في شكل جذوع الأشجار بعين الاعتبار من خلال تقدير ما يدعى بمعامل الشكل Form Factor. تهدف هذه الدراسة إذاً إلى تصميم موديل (نموذج) رياضي لحساب معامل الشكل لأشجار الصنوبر البروتي في منطقة ربيعة في شمال اللاذقية ما يمكن أن يساعد الحراجيين في تقدير حجم الأشجار والمجموعات الحرجية بشكل أكثر دقةً. خلال الفترة 2008-2011 تم قطع 72 شجرة صنوبر بروتي تتنوع في أعمارها وقياساتها وتقع في مجموعات حرجية طبيعية متنوعة في كثافتها وخصوبة مواقعها. تم قياس أقطار الأشجار المقطوعة على ارتفاعات مختلفة، كما تم حساب حجومها وحجوم الأسطوانات المكافئة لها ومن ثم الحصول على قيم معامل الشكل. تم استخدام 75% (55 شجرة) من البيانات الناتجة لتصميم موديل معامل الشكل و 25% (17 شجرة) منها لاختبار جودة الموديل. تم الحصول على موديل معامل الشكل باستخدام معادلات الانحدار غير الخطي Nonlinear Regression في البرنامج الإحصائي SPSS وقد بلغت قيمة معامل التحديد المعدل (R²adj =0.81). بلغت قيمة المتوسط النسبي لخطأ الموديل أثناء اختبار جودة الموديل ( =17.9%)، كما بلغت قيمة دقة الموديل (= 22.9%). للحصول على قيمة خطأ أقل ودقة أعلى للموديل ينصح باستخدام قاعدة بيانات أوسع لتشمل جميع مناطق انتشار الصنوبر البروتي في سوريا. Estimation of tree and stand volume is a key calculation for productive forest management (de Miguel et al., 2012). A precise estimation of tree volume needs to take the variation in bole forms into account while calculation, this can be done by estimating tree form factor. This study aims to construct a mathematical model to calculate the form factor of brutia pine trees grown in the regions of Rabiaa in northern Latakia. The form factor model can help foresters to precisely estimate the volume of tree and forest stands. During the period 2008-2011, 72 pine trees of various ages and sizes, located in natural stands of different densities and site qualities, were felled. Diameters at different heights of the felled trees were measured; trees volumes and volumes of equivalent cylinders were calculated, and consequently the values of tree form factor were computed. The dataset was randomly split into two parts, 75% (55 trees) of the data for constructing form factor model and 25% (17 trees) for model validation. A form factor model was obtained using the non-linear regression equations in the statistical program SPSS. Value of the coefficient of determination adjusted (R²adj) was about 0.81. The model has been validated using several statistical methods, the relative bias () was ca. 17.9%, while the value of model accuracy ) ) was 22.9 %. In order to obtain lower value of model relative bias and higher value of accuracy it’s recommended to use a larger database comprising all distribution areas of pine in Syria.